2008
DOI: 10.1007/s00217-008-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Turkish olive oils with respect to cultivar, geographic origin and harvest year, using fatty acid profile and mid-IR spectroscopy

Abstract: Fatty acid composition and mid-infrared spectra of olive oils in combination with chemometric techniques were used in the classiWcation of Turkish olive oils with respect to their varieties, growing location and harvest year. In particular, olive oil samples belonging to Wve diVerent cultivars were obtained from the same orchard in the middle part of Aegean region and two of these varieties were also received from another orchard in northern part of the same region of Turkey in two consecutive harvest years. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
53
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 20 publications
17
53
3
4
Order By: Relevance
“…The distribution of fatty acids in the oils of domestic cultivars was in agreement with those of authors working on Turkish olive oil varieties (Ersoy et al 2001;Dıraman and Hı7ıl 2004;Tous et al, 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009) and these values for foreign cultivars were similar to those reported for foreign olive oil varieties (Gutiérréz et al 1999;Gimeno et al 2002;Ollivier 2003;Poiana and Mincione 2004;Tous et al 2005). (Figure 2) based on their fatty acid profiles.…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
See 3 more Smart Citations
“…The distribution of fatty acids in the oils of domestic cultivars was in agreement with those of authors working on Turkish olive oil varieties (Ersoy et al 2001;Dıraman and Hı7ıl 2004;Tous et al, 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009) and these values for foreign cultivars were similar to those reported for foreign olive oil varieties (Gutiérréz et al 1999;Gimeno et al 2002;Ollivier 2003;Poiana and Mincione 2004;Tous et al 2005). (Figure 2) based on their fatty acid profiles.…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
“…The linolenic acid (18:3 n-3) level of the oils from domestic and foreign cultivars was below the maximum value fixed by the IOOC (1.0%) and by the Turkish Codex and EU (0.9 %). These findings on linolenic acid are in agreement with the results found in various producing countries of the Mediterranean basin (Gutiérréz et al 1999;Ersoy et al 2001;Gimeno et al 2002;Ollivier et al 2003;Dıraman and Hı7ıl 2004;Tous et al 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009). The linolenic acid levels of olive varieties, Picholine, Arbequnia, Manzanilla and Leccino, cultivated in Moorocco were higher (more 1%) than our results (Al -Antari et al 2003).…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
See 2 more Smart Citations
“…Uma das maneiras de detectar a adulteração é monitorar a composição dos triacilglicerídeos (TAG) e ácidos graxos (AG). 6,7 A cromatografia gasosa de alta resolução a alta temperatura (HT-HRGC) é uma técnica adequada para análise dos TAG. [8][9][10] Hidrólise de TAG a partir de óleos e gorduras para obter glicerol e ácidos graxos (AG) é uma importante reação da indústria oleoquí-mica.…”
unclassified